Intestinal obstruction due to gallstone ileus: a case report - Vera-Portilla, Angel F. (2022)
Gallstone ileus (BI) is defined as intraluminal mechanical intestinal obstruction by one or more gallstones; who have emigrated through a biliodigestive fistula, established as a complication of cholelithiasis. We present the case of a 59-year-old woman with a history of arterial hypertension, with a preoperative tomographic diagnosis of intestinal obstruction due to biliary ileus (Rigler's triad), for which she underwent emergency surgery, deciding to perform an enterolithotomy and schedule her second intervention in two months. BI is an uncommon cause of intestinal obstruction in elderly patients, with high morbidity and mortality. It requires a high index of suspicion in the presence of intermittent intestinal obstruction and a history of biliary colic. Rigler's triad is only present in a third of patients, for which tomography is the study of choice. Treatment is controversial, but the most widely used is enterolithotomy.